Analisis Dinamika Regulasi Sekolah Bertaraf Internasional serta Implikasinya terhadap Pengembangan Pendidikan Islam di Indonesia - Abduh, Muhammad; Latif Nawawi, Muhammad; Khodijah, Nyayu; Abdurahmansyah, Abdurahmansyah (Al-Bustan: Jurnal Pendidikan Islam, 2024)
The dynamic regulatory landscape presents significant challenges for International Standard Schools (SBI) in Indonesia, impacting their ability to meet global educational standards while integrating local cultural values. This study aims to explore the regulatory challenges faced by SBIs and their implications for educational quality and cultural integration. The method used is library research, which involves reviewing relevant literature and studies on regulations and the implementation of international standard programs. The findings reveal that although SBIs strive to provide high-quality education and facilities in line with international standards, they are often hindered by fluctuating regulations and inadequate financial support. Additionally, the study highlights the importance of a consistent and supportive regulatory framework, sustainable funding sources, and the adoption of an inclusive curriculum that respects local cultural values. These insights offer valuable implications for policymakers, educational institutions, and stakeholders, emphasizing the need for collaborative efforts to enhance the stability and effectiveness of SBIs in Indonesia. By addressing these challenges, SBIs can better fulfill their role in providing internationally competitive education while preserving Indonesia’s rich cultural heritage.